Transforming respiratory diseases management: a CMO-based hospital pharmaceutical care model - Zarate-Tamames, Borja; Garin, Noe; Calvin-Lamas, Marta; Jornet, Sonia; Martinez-Simon, Jose J.; Garcia-Gil, Sara; Garcia-Rebolledo, Eva M.; Morillo-Verdugo, Ramon (Frontiers in Pharmacology, 2024)
Introduction Respiratory diseases encompass a diverse range of conditions that significantly impact global morbidity and mortality. While common diseases like asthma and COPD exhibit moderate symptoms, less prevalent conditions such as pulmonary hypertension and cystic fibrosis profoundly affect quality of life and mortality. The prevalence of these diseases has surged by approximately 40% over the past three decades. Despite advancements in pharmacotherapy, challenges in drug administration, adherence, and adverse effects persist. This study aimed to develop and perform an interim validation of a Capacity-Motivation-Opportunity (CMO) model tailored for respiratory outpatients to enhance pharmaceutical care, which is the direct, responsible provision of medication-related care for the purpose of achieving definite outcomes that improve a patient’s quality of life, and overall well-being. Methodology This cross-sectional, multicenter study was conducted from March 2022 to March 2023. It comprised four phases: (1) forming an expert panel of 15 hospital pharmacists, (2) selecting respiratory pathologies based on prevalence and severity, (3) developing the CMO model's pillars, and (4) integrating and conducting an interim validation of the model. The Capacity pillar focused on patient stratification and personalized care; the Motivation pillar aligned therapeutic goals through motivational interviewing; and the Opportunity pillar promoted the use of information and communication technologies (ICTs) for telemedicine. Results The model included eight respiratory diseases based on expert assessment. For the Capacity pillar, 26 variables were defined for patient stratification, leading to three priority levels for personalized pharmaceutical care. In a preliminary test involving 201 patients across six hospitals, the stratification tool effectively classified patients according to their needs. The Motivation pillar adapted motivational interviewing techniques to support patient adherence and behavior change. The Opportunity pillar established teleconsultation protocols and ICT tools to enhance patient monitoring and care coordination. Conclusion The CMO model, tailored for respiratory patients, provides a comprehensive framework for improving pharmaceutical care. By focusing on patient-centered care, aligning therapeutic goals, and leveraging technology, this model addresses the multifaceted needs of individuals with respiratory conditions. Future studies are necessary to validate this model in other healthcare systems and ensure its broad applicability.